Engineering study on fracturing high-level hard rock strata by ground hydraulic action. (April 2019) - Yu, Bin; Gao, Rui; Kuang, Tiejun; Huo, Bingjie; Meng, Xiangbin
Abstract: The underground mining of extra-thick coal seams causes substantial migration of the overburden and generates extreme ground pressures. In view of the strong ground pressures produced by breakages and instabilities in high-level hard strata and the difficulties in their containment, we proposed an innovative solution to fracture high-level hard strata by ground hydraulic fracturing (GHF). Taking a 20 m thick coal seam in Tashan coal mine (Datong mine area, China) as an example, in situ ground hydraulic action experiments on the high-level hard rock strata was performed. In-situ measurements was performed to determine the key strata (KS) to be hydraulic fractured, and KS3 and KS4 were selected to be the target strata which were 110 m and 145 m away vertically above the coal seam, respectively. Fracturing was then performed using vertical wells. Micro-seismic measurements showed that the hydraulic fissure in KS3 is 250 m long, whereas 218 m in KS4. The fractured regions are 30–120 m in width. The hydraulic fissures in KS3 and KS4 exhibit an interlaced pattern that enhances the fracturing effect. Ground hydraulic action changed the fracturing structures of the high-level rock strata, thereby relieving the stress concentration around the working face. No strong strata behavior was observed on the working face after fracturing. The forces exerted on the supports was significantly reduced and the deformation of advanced roadways was controlled. This first-time field GHF experiment to control the strong strata behavior was successful, paving the way for new possibilities to high-level hard strata control for safety mining.